The emotions experienced by family medicine residents and interns during their clinical trainings: a qualitative study - HIDIROĞLU, SEYHAN; YILDIZ İNANICI, SİNEM; GÜLPINAR, MEHMET ALİ (My University, 2023)
Background: The family medicine residents and final year medical students are challenged with increased workload and they experience various emotions during their clinical trainings. They are confronted with uncertainties in their role descriptions and they witness illness, suffering and deaths as part of their everyday duties which may lead to burnout. Only several studies have focused on these experiences to find out what the family medicine residents and medical students were literally feeling. Aim: The aim of this study was to explore the family medicine residents’ and final year medical students’ emotions during their clinical trainings. Method: This qualitative study was performed with 15 family medicine residents and 24 final-year medical students using a convenience sample from two medical faculties to explore and analyze their emotions. Data were gathered by means of focus group interviews, including six interviews conducted and recorded through online meetings. Data were analyzed for themes using a thematic analysis approach. Since the interviews reached saturation in terms of content, the interviews were terminated at the end of sixth focus group meetings. Each interview took an average of 45–60 min. Results: Three main themes emerged from the data regarding residents’ and interns’ emotions. These were the \"clinical climate’s role\", \"emotions during patient encounters\" and \"coping strategies with negative emotions\". The most commonly encountered emotions were tension and anxiety followed by frustration and uncertainty. Conclusions: The family medicine residents and final-year medical students are challenged with emotions during their clinical trainings. Therefore, medical educators have to be aware of the need to support them in reflecting their emotions by prioritizing residents’and interns’ well-being
Keywords: Tıp; Tıp Eğitimi; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Medicine Education; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIBBİ ETİK; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL ETHICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine